2018
DOI: 10.5603/fm.a2017.0112
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral artery anatomical variations and aneurysms: a retrospective study based on computed tomography angiography findings

Abstract: The most common configuration of MCA is bifurcation before the genu with no dominating post-division trunk. Incidence of MCA aneurysms is not correlated with anatomical variations of MCA and the circle of Willis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 19 publications
2
22
0
2
Order By: Relevance
“…In the current study, no association was found between the CW configuration and presence of aneurysms (p=0.567). These findings are similar to a retrospective cerebral CTA study by P. Brzegowy et al which showed no association between anatomic variations of the MCA and CW with aneurysms [40].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, no association was found between the CW configuration and presence of aneurysms (p=0.567). These findings are similar to a retrospective cerebral CTA study by P. Brzegowy et al which showed no association between anatomic variations of the MCA and CW with aneurysms [40].…”
Section: Discussionsupporting
confidence: 91%
“…Branches sprouting from the main artery had different termination patterns (Table 1) ; of these, bifurcation was the most common (72%), consistent with previous reports [19][20][21][22][23][24]. Early bifurcation, defined as occurring within 1 cm of the MCA origin [13], was observed in 3% (Figure 2(d) and Table 1) and should be distinguished from double MCA.…”
Section: Resultssupporting
confidence: 85%
“…Theo P.T.Hà [7], ĐKTB của ICA trái là 4,71±0,62mm; phải là 4,68±0,56mm; theo J.Krejza [15] Theo bảng 3.4: khi nghiên cứu về MCA, R.Jeyakumar [17] có cách phân chia M1, thân trên (M2 trên), thân dưới (M2 dưới) tương tự như nhóm nghiên cứu của chúng tôi, tuy nhiên các tác giả chỉ đánh giá số đo M1, các đoạn khác chưa được nghiên cứu đến. P.Brzegowy [18] đưa ra kết quả đường kính của M1 T là 17mm; M1 P là 16,9; V.Rohan [19] đưa ra kết quả đường kính chung của đoạn M1 là 15,4mm. Theo kết quả nêu trên, đoạn M1 trong nghiên cứu của chúng tôi có giá trị cao hơn các tác giả khác có thể do phương tiện nghiên cứu, cỡ mẫu và chủng tộc khác nhau.…”
Section: Phương Pháp Nghiên Cứuunclassified
“…Theo kết quả nêu trên, đoạn M1 trong nghiên cứu của chúng tôi có giá trị cao hơn các tác giả khác có thể do phương tiện nghiên cứu, cỡ mẫu và chủng tộc khác nhau. P.Brzegowy [18] áp dụng MSCT đánh giá kích thước MCA và các biến đổi trên 250 bệnh nhân người châu Âu có phình mạch não và đưa ra khoảng cách MCA từ nguyên ủy đến vị trí gối (the distance from ICA division to MCA genu) là 24.2 mm (95% CI 23.9-24.5). V.Rohan [19], ứng dụng MSCT đánh giá 80 bệnh nhân châu Âu bị nhồi máu não, R.Jeyakumar [17] Theo bảng 3.6: Về mặt giải phẫu học, xét cả tiêu chí ĐKTB và CDTB, ICA đoạn trong sọ ngoài màng cứng của nhóm tuổi > 60 lớn hơn nhóm ≤60 (p<0,05).…”
Section: Phương Pháp Nghiên Cứuunclassified